Investor's Inattention and Earnings Announcement Effects on Tomb-Sweeping Day in China - Qingchen Feng; Dengyun Ning; Wan Zhang; Rui Zhou (Credit and Capital Markets – Kredit und Kapital, 2022)
This study investigates the relationship between investor inattention and earnings announcement effects around a Chinese holiday called Tomb-Sweeping Day, which, unlike other holidays, is short. Not only is investor attention distracted, which can generate emotional fluctuation, but a large number of listed companies issue earnings announcements within two days before the holiday. Using a sample of listed firms from 2008 to 2019 that released earnings announcements on Tomb-Sweeping Day, we first find that earnings announcement effects exist around Tomb-Sweeping Day, which are not studied in the previous literature. Second, because investors are more inclined to ignore negative earnings information around the holiday, we find stronger post drift from negative earnings announcements than from positive ones, in contrast to the conventional view. Finally, we confirm that investor inattention causes earnings announcement effects, providing further evidence to support behavioural finance theory.
Keywords: G14; G41; 330; earnings announcement effect; investor inattention; Tomb-Sweeping Day